Theory of knowledge : course companion - Dombrowski, Eileen; Bick, Mimi.; Lagemaat, Richard van de.; Rotenberg, Lena. (New York : Oxford University Press, 2007)
A resource for students participating in the International Baccalaureate Diploma Programme that provides content and activities which encourage thinking about learning, reflection, discussion, critical thinking, and exploration of topics.
"IB diploma programme."
Accompanies Theory of knowledge for the IB Diploma. Richard van de Lagemaat.
Includes bibliographical references (p. 297-305).
Adult
Keywords: Knowledge, Theory of; IB programme -- TOK; Theory of knowledge